Case Report: A rare case of multicentric angiosarcomas of bone mimicking multiple myeloma on 18F-FDG PET/CT - Huang, Wenpeng; Xiao, Xiaoyan; Zhang, Yongbai; Peng, Yushuo; Song, Lele; Li, Liming; Gao, Jianbo; Kang, Lei (Frontiers in Medicine, 2023)
Background: Angiosarcoma, a rare endothelial-origin tumor, can develop throughout the body, with the head and neck skin being the most commonly affected areas. It can also originate in other sites such as the breast, iliac artery, and visceral organs including the liver, spleen, and kidneys. Angiosarcoma of the bone is remarkably rare, presenting as either unifocal or multifocal bone lesions and often leading to a grim prognosis. Diagnosing bone angiosarcoma poses a significant challenge. 18 F-FDG PET/CT serves as a reliable and indispensable imaging modality for evaluating distant metastases and clinically staging angiosarcomas.Case Report: A 57-year-old woman presented with a 10-day history of dizziness and headaches.Cranial CT scan revealed bone destruction of the parietal bone, accompanied by soft tissue lesions, protruding into the epidural space. MRI examination demonstrated lesions with slightly elevated signal intensity on T2FLAIR, showing moderate enhancement. Furthermore, multiple foci were observed within the T12, L1-5, and S1-2 vertebrae, as well as in the bilateral iliac bones. For staging, 18 F-FDG PET/CT was performed. The MIP PET showed multifocal FDG-avid lesions in the sternum, bilateral clavicles, bilateral scapulae, multiple ribs, and pelvic bones. Heterogeneous FDG uptake was observed in multiple bone lesions, including intracranial (SUVmax = 11.3), right transverse process of the T10 vertebra (SUVmax = 5.8), ilium (SUVmax = 3.3), and pubis (SUVmax = 4.7). The patient underwent surgical resection of the cranial lesion. The pathological diagnosis was made with a highly differentiated angiosarcoma.Angiosarcoma of bone on FDG PET/CT scans is characterized by abnormal FDG uptake along with osteolytic destruction. This case highlights that angiosarcoma of bone can manifest as multicentric FDG uptake, resembling the pattern seen in multiple myeloma. FDG PET/CT can be a useful tool for staging this rare malignant tumor, offering the potential to guide biopsy procedures towards the most metabolically active site. And it should be considered in the differential diagnosis of multiple osteolytic lesions, including metastatic carcinoma, multiple myeloma, and lymphoma of bone.